THE HISTORY OF THE NAVAL MESS (UNION HOTEL) PRETORIA - Bredenkamp, J.D. (Scientia Militaria - South African Journal of Military Studies, 2012)
Naval Headquarters moved from Simonstown to Pretoria in January 1977. The then SA Naval Headquarters Unit was there ’to support the Chief of the Navy and his five Chiefs of Naval Staff and their Staff Officers in matters pertaining to personnel, administration, operations, logistics, intelligence and finance as well as most naval matters related to the inland area’. During the period 1977 to 1979, members of the HQ Unit were accommodated in mainly the Air Force Officers and NCO Messes till the Union Hotel was purchased in 1979.